Exploring non‑conventional irrigation methods and drone‑based monitoring to enhance water use efciency: a case of rice cultivation in Colombia - Martínez Vega, Ronald Ricardo; Ouazaa, Sofane; De Swaef, Tom; Chaali, Nesrine; Garré, Sarah; Jaramillo Barrios, Camilo Ignacio; Moreno Fonseca, Liz Patricia (Springer Science and Business Media Deutschland GmbH, 2025)
Climate variability in Colombia threatens water supplies for rice and other crops, highlighting the urgent need for efficient irrigation techniques. This study was conducted over three growing seasons in the Tolima region and evaluated three irrigation techniques: cascade distribution (CD), multiple inlet rice irrigation (MIRI), and alternate wetting and drying combined with MIRI (AWD + MIRI). The focus was on optimizing water usage, sustaining grain yield, and leveraging vegetation indices for irrigation monitoring. Key findings revealed that visual soil moisture monitoring in light-textured soils enabled substantial irrigation reductions. MIRI reduced water usage by 22%–54%, while AWD + MIRI achieved reductions of 48%–65% compared to CD, with no significant grain yield loss. CD, however, demonstrated the lowest water productivity. Vegetation indices measured peaked during the reproductive stage, aligning with maximum biomass. Notably, MIRI consistently exhibited superior vegetation index values, particularly in growing season 2 (GS2) and growing season 3 (GS3), whereas CD underperformed. Variability analyses highlighted Greener area (GGA) as a more sensitive index, whereas Normalized Difference Vegetation Index (NDVI) demonstrated a lower capacity to capture crop variability for irrigation monitoring. These findings emphasize that adopting the most water-efficient irrigation method identified in this study, AWD + MIRI, coupled with GGA monitoring, can enhance water use efficiency without compromising yield. This approach offers a sustainable path forward for Colombian rice cultivation under the growing pressures of climate variability.